2019
DOI: 10.3390/met9040412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificial Defects on the Very High Cycle Fatigue Behavior of 316L Stainless Steel

Abstract: Widely used for structural materials in nuclear engineering, 316L austenitic stainless steel undergoes very high cycle fatigue (VHCF) throughout its service life. Since defects caused by service conditions are unavoidable in many engineering components during service life, the effects should be properly understood. In the present study, the effect of surface defects on the VHCF behavior were investigated on solution annealed (SA) and cold-worked (CW) 316L. Surface defects were artificially created using indent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…S-N diagram of the L-PBF 316L stainless steel specimens, as well as the data obtained by Spierings et al[35], Leuders et al[36], and by Xiong et al[41] for cold-worked and solution-annealed 316L SS. The points indicated by the arrows correspond to specimens that were not disrupted during the tests.Materials 2020, 13, x FOR PEER REVIEW 6 of 12…”
supporting
confidence: 68%
See 2 more Smart Citations
“…S-N diagram of the L-PBF 316L stainless steel specimens, as well as the data obtained by Spierings et al[35], Leuders et al[36], and by Xiong et al[41] for cold-worked and solution-annealed 316L SS. The points indicated by the arrows correspond to specimens that were not disrupted during the tests.Materials 2020, 13, x FOR PEER REVIEW 6 of 12…”
supporting
confidence: 68%
“…As shown in Figure 3, the plotted S-N data corresponding to cold-worked specimens [41] shows higher endurance at similar stress levels than the data in the plot obtained for the AM specimens in HCF [36] and VHCF regimes. However, the AM specimens demonstrated almost the same fatigue behavior as the specimens heat treated at 1120 • C for 7.5 min followed by water quenching [41]. This indicated that the difference could be explained by assuming features of the damage-to-failure mechanism of the AM and routinely manufactured 316L stainless steel under fatigue loading.…”
Section: S-n Curves Of the Specimensmentioning
confidence: 52%
See 1 more Smart Citation
“…Although there are several works where artificial surface defects were used for VHCF studies, [ 12,32 ] there is only one very recent work in which it was used for AM materials. [ 33 ] The authors used spherical artificial defects of sizes Area in the range from 100 to 400 μm in Ti6Al4V.…”
Section: Introductionmentioning
confidence: 99%
“…The VHCF properties are thus a vital indicator to assess the security of these aero-engine components. Therefore, the VHCF performance of titanium alloys and their damage mechanisms have received extensive attention over recent decades [2][3][4].…”
Section: Introductionmentioning
confidence: 99%